Synthesis, Characterization and ESR Studies of Zn1-x Co x O Nanoparticles - Arda, L.; Acikgoz, M.; Dogan, N.; Akcan, D.; Cakiroglu, O. (Springer, 2014)
Zn1-x Co (x) O polycrystalline nanoparticles with different (x=0.03, 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3) compositions were synthesized using the sol-gel technique. The effects of doping ratio and annealing temperature on structure and magnetic properties were investigated systematically. The phase, crystal structure, and microstructure of the Zn1-x Co (x) O nanoparticles were characterized using X-Ray diffraction and scanning electron microscope. Electron spin resonance spectra of Zn1-x Co (x) O nanoparticles were collected at room temperature on a Bruker EMX model X-band spectrometer operating at a frequency of 9.50 GHz.
Keywords: Magnetic materials; Microstructure; Sol-gel growth; Magnetic properties